Constraining the time of outburst of an optical nova candidate in M 31 - Henze, M.; Kaduk, F.; Pietsch, W.; Burwitz, V.; Liakos, A.; Hatzidimitriou, D.; Niarchos, P. (2009)
We confirm a nova candidate in M 31 reported to us by K. Nishiyama and F. Kabashima and present a pre-discovery detection that allows us to tightly constrain the time of outburst for this object. The nova candidate was discovered by Nishiyama and Kabashima (Miyaki-Argenteus observatory, Japan) on 2009 September 3.752 UT, with no object visible at its position on September 1.566 UT (private communication).
Keywords: Novae; Optical